Nuclear power's contribution to UAE's decarbonization pathways: a lifecycle assessment perspective. - Acquaye, Adolf; Alzaabi, Mariam Manea Hamad Eisa; Foulon, Francois; Addad, Yacine (Journal of Industrial Ecology, 2026)
The energy trilemma framework, which balances energy security, environmental sustainability, and energy equity, underpins the UAE's National Energy Strategy 2050, which seeks to diversify the energy mix and reduce carbon emissions. As part of this strategy, the UAE has pursued peaceful nuclear energy to generate low-carbon electricity and improve performance across all three dimensions of the trilemma. In 2024, the final unit of the Barakah Nuclear Power Plant, a Generation III + APR1400 facility entered commercial operation. While nuclear energy is widely considered a low-carbon source, life cycle assessment (LCA) studies have shown significant variability in emissions, with reported interquartile ranges between 47 and 220 gCO/kWh. Moreover, few LCA studies focus on nuclear plants operating in arid or Middle Eastern contexts, creating a gap in region-specific data necessary for evidence-based policymaking. To address this, the study applies a Hybrid LCA to quantify the full direct and indirect carbon emissions associated with Barakah's 60-year operational life. Results estimate lifecycle emissions at 6.35 gCO/kWh, well below typical global averages. A scenario analysis comparing the current 18-month refueling cycle with an alternative 24-month cycle highlights opportunities for operational optimization and further emissions reduction. A sensitivity analysis also examines the influence of temporal boundaries on results. The findings not only demonstrate Barakah's contribution to the UAE's decarbonization goals but also provide a transparent benchmark for nuclear performance in similar regional and technological contexts. This study supports the development of targeted, data-driven energy policy and enhances understanding of nuclear energy's lifecycle sustainability.